Complaints Commissioners’ Assistance Function: System Navigator or Queue Jumper? - Laliberté, Maude; Brisson, Julien; Lemoine, Marie-Eve; Payment, Jean-Philippe; Blackburn, Emilie (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
This commentary invites reflection on the positive and negative outcomes of “assistances” provided by a Complaints Commissioner. While the goal of an assistance is to help the user navigate the health system, a lack of clarity and understanding of the process can lead to the user obtaining undue privileges. We suggest three key values to guide the equitable conduct of assistances and we suggest a mixed method research methodology to document the positive and negative impacts of assistances.